IMMUNOHISTOCHEMICAL STUDY OF THE BCL-2 GENE EXPRESSION IN THE WHITE RATS’ SPLEEN TISSUE IN CONDITIONS OF INDUCED ONCOGENESIS - Лісничук, Н.Є.; Soroka, Yu.V.; Андрійчук, І.Я.; Nebesna, Z.M.; Volkov, K.S.; Стравська, М.Я.; Yavorska, S.I.; Darmorys, I.V. (World of Medicine and Biology, 2019)
Introduction Bcl-2 proteins play a central role in the regulation of cell death and have the ability to regulate its various forms, including apoptosis, necrosis and autophagy, and thus serve as nodal points when converging several ways of cell death that is widely related to oncology. There is considerable evidence that the regulation of encoding genes, or antiapoptotic, or pro-apoptotic proteins of the Bcl-2 family, varies from cancer. The ability of anti-apoptotic proteins of the Bcl-2 group to suppress cell death from cytotoxic antitumor drugs makes these proteins particularly interesting as a potential target for cancer diagnosis. Bcl-2 works at the distal point of the conservative pathway of cell death, which is used by most antitumor drugs, which is a form of internal chemo-resistance, which differs from previously discovered mechanisms. Therefore, determining the degree of expression of a number of proteins in the group of Bcl-2 has an important prognostic value for many types of cancer treated with chemotherapeutic drugs. The aim of the study. In view of the foregoing, the purpose of this experimental study was to determine the degree of expression of the Bcl-2 gene in the spleen of white rats tissues under conditions of development of the adenocarcinoma of the large intestine induced by a long (30 weeks observation) induction of dimethylhydrazine, dihydrochloride. Materials and methods of research. The study was conducted on 168 adult white rats. All manipulations with experimental animals were conducted in accordance with the rules of the "European convention for the protection of vertebrate animals used for research and other scientific purposes", as well as "Scientific and practical recommendations for maintenance and operation of laboratories". Carcinogenesis was modeled by the injection of 1,2-dimethylhydrazine dihydrochloride (DMG) (Chemie Sigma-aldrich, Japan) dissolved in isotonic sodium chloride solution. Carcinogens are subcutaneously injected into the intermixture portion at a dose of 7.2 mg / kg once per week for 30 weeks, clearly based on the weight of the animal at the rate of 0.1 ml of DMH solution per 10 grams of body weight. For staining with immunohistochemistry, pieces of the spleen are fixed in a 10% neutralized formalin buffer solution (pH 7.2-7.4). Platinum ELISA (Austria) was used to determine the Bcl-2 gene as one of the major apoptotic inhibitors responsible for maintaining cellular stability in populations. Results of the research and their discussion. In animals of the control group there was diffuse, expressed positive cytoplasmic reaction (+ +) in red pulp of the spleen of the antibody Bcl-2 Oncoprotein (Clone 124) and a moderate positive reaction was observed in the isolated cells of the germinal center of the lymphoid node. In the dynamics of the experiment (10 weeks from the beginning of the onco-process modeling), an increase in the number of cells expressing the Bcl-2 gene in red pulp, depending on the time of detection of the oncogenic factor, is observed, while maintaining the intensity of the reaction (+ + +). In white pulp there is a moderately pronounced positive reaction (+ - -) in single cells, scattered around the periphery of the entire germinal center and periarteriolar zone of the lymphoid nodule. 20 weeks after the introduction of carcinogen into the spleen tissue of experimental animals, the number of cells expressing the gene significantly increases. Bcl-2, on the border of periarteriolar zones with marginal zones of lymphoid nodules of white pulp and in the most red pulp, maintaining the intensity of the reaction. In the embryonic center of the lymphoid node, the positive reaction is moderately expressed, the cytoplasmic type of expression (+ - -) is observed in single cell scattered along its periphery, and the expressed positive reaction, the cytoplasmic type of expression (+ - -) from numerous diffusely scattered and microgroups of cells on periarteriolar zone of the edge with marginal zone of lymphoid pupils of white pulp. 30 weeks after the start of the modeling of the large intestine adenocarcinoma, a positive reaction, a cytoplasmic type of expression (+ +) of cells in red pulp, which is bordered by white and a pronounced positive reaction, a cytoplasmic type of expression (+ +) in cells of germinal centers and mantle zones of lymphoid nodules of white pulp. Conclusions 1. Increased level of expression of BCL-2 gene by cells of structural components of the spleen, depending on the time of exposure of the oncogenic factor and changes in morphological organization of the investigated organ. The development of chronic neoplastic endotoxemia syndrome, expressed vascular disorders in the spleen tissue, degeneration and destruction of lymphoid tissue are accompanied by an increase in the number of cells expressing the Bcl-2 gene in a red pulp and the spread of high-expression zones in a white pulp. 2. Dynamics of immunohistochemical changes in white spleen tissue in conditions of induced oncogenesis indicates a significant violation of the physiological functioning of the investigated organ, which can significantly affect both the development of the neoplastic process and the results of cytostatic correction.